Lessons from the Total Synthesis of Highly Substituted Benzophenone Natural Products - Münzer, Lukas; Schmalz, Hans-Günther (Synlett, 2023)
In this account, we summarize the results and experience gained during 20 years of research in the field of polyketidic natural products displaying a tetra-ortho-substituted benzophenone substructure. As demonstrated by the various approaches towards mumbaistatin and pestalone as targets of high biological relevance, the synthesis of such systems is surprisingly difficult due to the intense interactions of the functional groups adjacent to the ketone bridge. We report successes and failures, as well as the discovery of surprising reactivities that are important for understanding the non-enzymatic formation of related compounds in Nature.1 Introduction2 Mumbaistatin3 Pestalone4 Conclusion
Keywords: benzophenones; mumbaistatin; pestalone; phthalides; isoindolinones; carbonyl–olefin metathesis; coupling reactions